# Calculator search results

Formula
Number of solution
Relationship between roots and coefficients
Graph
$y = x ^ { 2 } + \left ( 13 - x \right ) ^ { 2 }$
$y = 89$
$y$Intercept
$\left ( 0 , 169 \right )$
Minimum
$\left ( \dfrac { 13 } { 2 } , \dfrac { 169 } { 2 } \right )$
Standard form
$y = 2 \left ( x - \dfrac { 13 } { 2 } \right ) ^ { 2 } + \dfrac { 169 } { 2 }$
$x ^{ 2 } + \left( 13-x \right) ^{ 2 } = 89$
$\begin{array} {l} x = 8 \\ x = 5 \end{array}$
Find solution by method of factorization
$x ^ { 2 } + \left ( 13 - x \right ) ^ { 2 } = \color{#FF6800}{ 89 }$
 Move the expression to the left side and change the symbol 
$x ^ { 2 } + \left ( 13 - x \right ) ^ { 2 } \color{#FF6800}{ - } \color{#FF6800}{ 89 } = 0$
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \left ( \color{#FF6800}{ 13 } \color{#FF6800}{ - } \color{#FF6800}{ x } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 89 } = 0$
 Expand the expression 
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 26 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 80 } = 0$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 26 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 80 } = 0$
$acx^{2} + \left(ad + bc\right)x +bd = \left(ax + b\right)\left(cx+d\right)$
$\color{#FF6800}{ 2 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 8 } \right ) \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \right ) = 0$
$\color{#FF6800}{ 2 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 8 } \right ) \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \right ) = \color{#FF6800}{ 0 }$
 If the product of the factor is 0, at least one factor should be 0 
$\begin{array} {l} \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 8 } = \color{#FF6800}{ 0 } \\ \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 5 } = \color{#FF6800}{ 0 } \end{array}$
$\begin{array} {l} \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 8 } = \color{#FF6800}{ 0 } \\ \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 5 } = \color{#FF6800}{ 0 } \end{array}$
 Solve the equation to find $x$
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ 8 } \\ \color{#FF6800}{ x } = \color{#FF6800}{ 5 } \end{array}$
$\begin{array} {l} x = 8 \\ x = 5 \end{array}$
Solve quadratic equations using the square root
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \left ( \color{#FF6800}{ 13 } \color{#FF6800}{ - } \color{#FF6800}{ x } \right ) ^ { \color{#FF6800}{ 2 } } = 89$
 Organize the expression 
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 26 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 169 } = 89$
$2 x ^ { 2 } - 26 x + 169 = \color{#FF6800}{ 89 }$
 Move the expression to the left side and change the symbol 
$2 x ^ { 2 } - 26 x + 169 \color{#FF6800}{ - } \color{#FF6800}{ 89 } = 0$
$2 x ^ { 2 } - 26 x + \color{#FF6800}{ 169 } \color{#FF6800}{ - } \color{#FF6800}{ 89 } = 0$
 Subtract $89$ from $169$
$2 x ^ { 2 } - 26 x + \color{#FF6800}{ 80 } = 0$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 26 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 80 } = \color{#FF6800}{ 0 }$
 Divide both sides by the coefficient of the leading highest term 
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 13 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 40 } = \color{#FF6800}{ 0 }$
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 13 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 40 } = \color{#FF6800}{ 0 }$
 Convert the quadratic expression on the left side to a perfect square format 
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 13 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 40 } \color{#FF6800}{ - } \left ( \color{#FF6800}{ \dfrac { 13 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 0 }$
$\left ( x - \dfrac { 13 } { 2 } \right ) ^ { 2 } \color{#FF6800}{ + } \color{#FF6800}{ 40 } \color{#FF6800}{ - } \left ( \color{#FF6800}{ \dfrac { 13 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = 0$
 Move the constant to the right side and change the sign 
$\left ( x - \dfrac { 13 } { 2 } \right ) ^ { 2 } = \color{#FF6800}{ - } \color{#FF6800}{ 40 } \color{#FF6800}{ + } \left ( \color{#FF6800}{ \dfrac { 13 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } }$
$\left ( x - \dfrac { 13 } { 2 } \right ) ^ { 2 } = - 40 + \left ( \color{#FF6800}{ \dfrac { 13 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } }$
 When raising a fraction to the power, raise the numerator and denominator each to the power 
$\left ( x - \dfrac { 13 } { 2 } \right ) ^ { 2 } = - 40 + \dfrac { \color{#FF6800}{ 13 } ^ { \color{#FF6800}{ 2 } } } { \color{#FF6800}{ 2 } ^ { \color{#FF6800}{ 2 } } }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 13 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ - } \color{#FF6800}{ 40 } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 13 ^ { 2 } } { 2 ^ { 2 } } }$
 Organize the expression 
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 13 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ \dfrac { 9 } { 4 } }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 13 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ \dfrac { 9 } { 4 } }$
 Solve quadratic equations using the square root 
$\color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 13 } { 2 } } = \pm \sqrt{ \color{#FF6800}{ \dfrac { 9 } { 4 } } }$
$\color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 13 } { 2 } } = \pm \sqrt{ \color{#FF6800}{ \dfrac { 9 } { 4 } } }$
 Solve a solution to $x$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ \dfrac { 3 } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 13 } { 2 } }$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ \dfrac { 3 } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 13 } { 2 } }$
 Separate the answer 
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 13 } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 3 } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 13 } { 2 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 3 } { 2 } } \end{array}$
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 13 } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 3 } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 13 } { 2 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 3 } { 2 } } \end{array}$
 Organize the expression 
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ 8 } \\ \color{#FF6800}{ x } = \color{#FF6800}{ 5 } \end{array}$
$\begin{array} {l} x = 8 \\ x = 5 \end{array}$
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \left ( \color{#FF6800}{ 13 } \color{#FF6800}{ - } \color{#FF6800}{ x } \right ) ^ { \color{#FF6800}{ 2 } } = 89$
 Organize the expression 
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 26 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 169 } = 89$
$2 x ^ { 2 } - 26 x + 169 = \color{#FF6800}{ 89 }$
 Move the expression to the left side and change the symbol 
$2 x ^ { 2 } - 26 x + 169 \color{#FF6800}{ - } \color{#FF6800}{ 89 } = 0$
$2 x ^ { 2 } - 26 x + \color{#FF6800}{ 169 } \color{#FF6800}{ - } \color{#FF6800}{ 89 } = 0$
 Subtract $89$ from $169$
$2 x ^ { 2 } - 26 x + \color{#FF6800}{ 80 } = 0$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 26 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 80 } = 0$
 Bind the expressions with the common factor $2$
$\color{#FF6800}{ 2 } \left ( \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 13 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 40 } \right ) = 0$
$\color{#FF6800}{ 2 } \left ( \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 13 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 40 } \right ) = \color{#FF6800}{ 0 }$
 Divide both sides by $2$
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 13 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 40 } = \color{#FF6800}{ 0 }$
$x = \dfrac { \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } 13 \right ) \pm \sqrt{ \left ( - 13 \right ) ^ { 2 } - 4 \times 1 \times 40 } } { 2 \times 1 }$
 Simplify Minus 
$x = \dfrac { 13 \pm \sqrt{ \left ( - 13 \right ) ^ { 2 } - 4 \times 1 \times 40 } } { 2 \times 1 }$
$x = \dfrac { 13 \pm \sqrt{ \left ( \color{#FF6800}{ - } \color{#FF6800}{ 13 } \right ) ^ { \color{#FF6800}{ 2 } } - 4 \times 1 \times 40 } } { 2 \times 1 }$
 Remove negative signs because negative numbers raised to even powers are positive 
$x = \dfrac { 13 \pm \sqrt{ 13 ^ { 2 } - 4 \times 1 \times 40 } } { 2 \times 1 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 13 \pm \sqrt{ 13 ^ { 2 } - 4 \times 1 \times 40 } } { 2 \times 1 } }$
 Organize the expression 
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 13 \pm \sqrt{ 9 } } { 2 \times 1 } }$
$x = \dfrac { 13 \pm \sqrt{ \color{#FF6800}{ 9 } } } { 2 \times 1 }$
 Organize the part that can be taken out of the radical sign inside the square root symbol 
$x = \dfrac { 13 \pm \color{#FF6800}{ 3 } } { 2 \times 1 }$
$x = \dfrac { 13 \pm 3 } { 2 \color{#FF6800}{ \times } \color{#FF6800}{ 1 } }$
 Multiplying any number by 1 does not change the value 
$x = \dfrac { 13 \pm 3 } { \color{#FF6800}{ 2 } }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 13 \pm 3 } { 2 } }$
 Separate the answer 
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 13 + 3 } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 13 - 3 } { 2 } } \end{array}$
$\begin{array} {l} x = \dfrac { \color{#FF6800}{ 13 } \color{#FF6800}{ + } \color{#FF6800}{ 3 } } { 2 } \\ x = \dfrac { 13 - 3 } { 2 } \end{array}$
 Add $13$ and $3$
$\begin{array} {l} x = \dfrac { \color{#FF6800}{ 16 } } { 2 } \\ x = \dfrac { 13 - 3 } { 2 } \end{array}$
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 16 } { 2 } } \\ x = \dfrac { 13 - 3 } { 2 } \end{array}$
 Do the reduction of the fraction format 
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 8 } { 1 } } \\ x = \dfrac { 13 - 3 } { 2 } \end{array}$
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 8 } { 1 } } \\ x = \dfrac { 13 - 3 } { 2 } \end{array}$
 Reduce the fraction to the lowest term 
$\begin{array} {l} x = \color{#FF6800}{ 8 } \\ x = \dfrac { 13 - 3 } { 2 } \end{array}$
$\begin{array} {l} x = 8 \\ x = \dfrac { \color{#FF6800}{ 13 } \color{#FF6800}{ - } \color{#FF6800}{ 3 } } { 2 } \end{array}$
 Subtract $3$ from $13$
$\begin{array} {l} x = 8 \\ x = \dfrac { \color{#FF6800}{ 10 } } { 2 } \end{array}$
$\begin{array} {l} x = 8 \\ x = \color{#FF6800}{ \dfrac { 10 } { 2 } } \end{array}$
 Do the reduction of the fraction format 
$\begin{array} {l} x = 8 \\ x = \color{#FF6800}{ \dfrac { 5 } { 1 } } \end{array}$
$\begin{array} {l} x = 8 \\ x = \color{#FF6800}{ \dfrac { 5 } { 1 } } \end{array}$
 Reduce the fraction to the lowest term 
$\begin{array} {l} x = 8 \\ x = \color{#FF6800}{ 5 } \end{array}$
 2 real roots 
Find the number of solutions
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \left ( \color{#FF6800}{ 13 } \color{#FF6800}{ - } \color{#FF6800}{ x } \right ) ^ { \color{#FF6800}{ 2 } } = 89$
 Organize the expression 
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 26 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 169 } = 89$
$2 x ^ { 2 } - 26 x + 169 = \color{#FF6800}{ 89 }$
 Move the expression to the left side and change the symbol 
$2 x ^ { 2 } - 26 x + 169 \color{#FF6800}{ - } \color{#FF6800}{ 89 } = 0$
$2 x ^ { 2 } - 26 x + \color{#FF6800}{ 169 } \color{#FF6800}{ - } \color{#FF6800}{ 89 } = 0$
 Subtract $89$ from $169$
$2 x ^ { 2 } - 26 x + \color{#FF6800}{ 80 } = 0$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 26 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 80 } = \color{#FF6800}{ 0 }$
 Determine the number of roots using discriminant, $D=b^{2}-4ac$ from quadratic equation, $ax^{2}+bx+c=0$
$\color{#FF6800}{ D } = \left ( \color{#FF6800}{ - } \color{#FF6800}{ 26 } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ 80 }$
$D = \left ( \color{#FF6800}{ - } \color{#FF6800}{ 26 } \right ) ^ { \color{#FF6800}{ 2 } } - 4 \times 2 \times 80$
 Remove negative signs because negative numbers raised to even powers are positive 
$D = 26 ^ { 2 } - 4 \times 2 \times 80$
$D = \color{#FF6800}{ 26 } ^ { \color{#FF6800}{ 2 } } - 4 \times 2 \times 80$
 Calculate power 
$D = \color{#FF6800}{ 676 } - 4 \times 2 \times 80$
$D = 676 \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ 80 }$
 Multiply the numbers 
$D = 676 \color{#FF6800}{ - } \color{#FF6800}{ 640 }$
$D = \color{#FF6800}{ 676 } \color{#FF6800}{ - } \color{#FF6800}{ 640 }$
 Subtract $640$ from $676$
$D = \color{#FF6800}{ 36 }$
$\color{#FF6800}{ D } = \color{#FF6800}{ 36 }$
 Since $D>0$ , the number of real root of the following quadratic equation is 2 
 2 real roots 
$\alpha + \beta = 13 , \alpha \beta = 40$
Find the sum and product of the two roots of the quadratic equation
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \left ( \color{#FF6800}{ 13 } \color{#FF6800}{ - } \color{#FF6800}{ x } \right ) ^ { \color{#FF6800}{ 2 } } = 89$
 Organize the expression 
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 26 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 169 } = 89$
$2 x ^ { 2 } - 26 x + 169 = \color{#FF6800}{ 89 }$
 Move the expression to the left side and change the symbol 
$2 x ^ { 2 } - 26 x + 169 \color{#FF6800}{ - } \color{#FF6800}{ 89 } = 0$
$2 x ^ { 2 } - 26 x + \color{#FF6800}{ 169 } \color{#FF6800}{ - } \color{#FF6800}{ 89 } = 0$
 Subtract $89$ from $169$
$2 x ^ { 2 } - 26 x + \color{#FF6800}{ 80 } = 0$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 26 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 80 } = \color{#FF6800}{ 0 }$
 In the quadratic equation $ax^{2}+bx+c=0$ , if the two roots are $\alpha, \beta$ , then it is $\alpha + \beta =-\dfrac{b}{a}$ , $\alpha\times\beta=\dfrac{c}{a}$
$\color{#FF6800}{ \alpha } \color{#FF6800}{ + } \color{#FF6800}{ \beta } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { - 26 } { 2 } } , \color{#FF6800}{ \alpha } \color{#FF6800}{ \beta } = \color{#FF6800}{ \dfrac { 80 } { 2 } }$
$\alpha + \beta = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { - 26 } { 2 } } , \alpha \beta = \dfrac { 80 } { 2 }$
 Solve the sign of a fraction with a negative sign 
$\alpha + \beta = \color{#FF6800}{ \dfrac { 26 } { 2 } } , \alpha \beta = \dfrac { 80 } { 2 }$
$\alpha + \beta = \color{#FF6800}{ \dfrac { 26 } { 2 } } , \alpha \beta = \dfrac { 80 } { 2 }$
 Reduce the fraction 
$\alpha + \beta = \color{#FF6800}{ 13 } , \alpha \beta = \dfrac { 80 } { 2 }$
$\alpha + \beta = 13 , \alpha \beta = \color{#FF6800}{ \dfrac { 80 } { 2 } }$
 Reduce the fraction 
$\alpha + \beta = 13 , \alpha \beta = \color{#FF6800}{ 40 }$
 그래프 보기 
Graph
Solution search results